A porous Fe2O3-Se@NC material and its preparation method and application

By loading selenium into a porous carbon material co-doped with nitrogen and Fe2O3, the problem of selenium deposition on the surface of the support material is solved, and the good recombination of Se and the composite is achieved, which significantly improves the electrochemical performance of Na-Se batteries.

CN115732685BActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110989831.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-26
Publication Date
2025-02-14
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively load selenium into a porous carbon carrier, resulting in selenium depositing on the surface of the carrier material, wasting selenium and affecting battery performance.

Method used

Selenium is loaded into a porous carbon material co-doped with nitrogen and Fe2O3 through the impregnation method, and a simple low-temperature stirring adsorption method is used to achieve good recombination between Se and the composite and avoid selenium waste.

Benefits of technology

The electrochemical performance of Na-Se batteries is significantly improved, uniform dispersion of Se particles and rapid electron and ion transmission are achieved, and the rate performance and cycle stability of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115732685B_ABST
    Figure CN115732685B_ABST
Patent Text Reader

Abstract

The present invention discloses a porous Fe2O3-Se@NC material and a preparation method and application thereof, belonging to the technical field of alkali metal batteries. First, Fe2O3@NC co-doped with nitrogen and Fe2O3 is prepared, and then Fe2O3@NC porous carbon material co-doped with nitrogen and Fe2O3 is obtained by acid hydrolysis, and selenium is loaded in the Fe2O3@NC porous carbon material co-doped with nitrogen and Fe2O3 by a simple impregnation method. While achieving physical confinement of polyselenides, the effect of polar forces on polyselenides can also be achieved, thereby significantly improving the electrochemical performance of Na-Se batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alkali metal batteries, and particularly relates to a porous Fe2O3-Se@NC material with high rate and high cycle stability, a preparation method thereof, and an application thereof as a negative electrode material for sodium ion batteries and potassium ion batteries. Background Art

[0002] With the increasing demand for electric vehicles and stationary energy storage systems, the development of post-charge battery systems with high energy and power density has attracted great research interest. Recently, sodium-ion batteries (SIBs) have emerged as a promising alternative to lithium-ion batteries because sodium resources are more abundant in nature compared to lithium resources. However, their energy density is still insufficient to meet the technical requirements for commercialization, so it is crucial to develop advanced electrode materials to broaden the application scope of SIBs. In this regard, sodium-selenium (Na-Se) batteries have received considerable attention. Unlike traditional intercalation cathodes, Se forms alloys with alkali metals and provides 675 mA hg -1 Although the specific capacity of Se is lower than that of S (1675 mA hg -1 ), but its volume capacity is comparable to that of S due to its high density (Se is 3253 mA h cm -3 , S is 3467mA h cm -3 In addition, Se (1×10 -3 S m -1 ) has a significantly higher conductivity than S(5×10 -28 S m -1 ), and the shuttling effect of polyselenides is not as serious as that of polysulfides.

[0003] Non-polar materials have been widely studied as selenium hosts to solve the problems encountered. Due to their excellent electrical conductivity, the use of non-polar carbon-based materials such as carbon nanotubes, carbon hollow nanospheres, carbon fiber cloth and conductive polymers as selenium hosts has attracted widespread interest and research to improve capacity and cycle reversibility. The preparation of carbon-based selenium electrodes requires treating solid selenium at high temperature (260°C) to convert it into a molten state, so that selenium can penetrate into the carrier material. However, since selenium maintains high viscosity and low fluidity in the molten state, it is difficult for selenium to quickly enter the carrier material. Most of the selenium is deposited on the surface of the carrier material, causing the carrier to lose its function of binding selenium. This synthesis method not only causes the loss of selenium, but also leads to poor performance of the synthesized composite material. Researching and developing a method to uniformly load selenium on a porous carbon carrier has become an important topic that needs to be studied urgently. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a porous Fe2O3-Se@NC material loaded with Se and a preparation method and application thereof. Selenium is loaded into a porous carbon material co-doped with nitrogen and Fe2O3 by a simple impregnation method, which can achieve physical confinement of polyselenides while also achieving the effect of polar forces on polyselenides, thereby significantly improving the electrochemical performance of Na-Se batteries.

[0005] The object of the present invention is achieved by the following methods:

[0006] A method for preparing a porous Fe2O3-Se@NC material mainly comprises the following steps:

[0007] (1) dissolving a polypropylene glycol and ethylene oxide addition polymer (F127) and dopamine hydrochloride (DA) in a mixed solution of water and alcohol to obtain a clear solution, adding an iron salt or its hydrate under stirring to form a clear solution, adding 1,3,5-benzenetricarboxylic acid, stirring and reacting for 10 to 150 minutes, centrifuging to obtain a separate product, washing it with a mixed solution of water and alcohol for at least 3 times, and drying to obtain polymer nanoparticles, placing the obtained polymer nanoparticles in a porcelain boat, raising the temperature to 500 to 800°C in an inert gas atmosphere, calcining for 2 to 5 hours, cooling to room temperature, and placing the porcelain boat in air for 20 to 60 minutes to obtain Fe2O3@NC;

[0008] (2) adding the Fe2O3@NC prepared in step (1) into an acid solution, stirring at 40-100° C. for 2-12 h, to obtain a porous nitrogen and Fe2O3 co-doped Fe2O3@NC composite material;

[0009] (3) Weigh the Fe2O3@NC composite material prepared in step (2) and add it to an organic solvent in which Se is dissolved, stir and evaporate to remove the organic solvent, and dry to obtain Fe2O3-Se@NC material.

[0010] Furthermore, in step (1), the mass ratio of the polypropylene glycol and ethylene oxide addition polymer (F127) to dopamine hydrochloride (DA) is 1:2 to 2:1, and the final concentration of the polypropylene glycol and ethylene oxide addition polymer (F127) is 1 to 50 g / L.

[0011] Furthermore, the alcohols described in step (1) include methanol, ethanol, propanol and butanol, and the volume ratio of water to alcohols is 1:2 to 2:1.

[0012] Furthermore, the iron salt in step (1) is one or more of ferric sulfate, ferric chloride, and ferric nitrate, and the final concentration of iron ions is 0.01 to 0.2 mol / L; the final concentration of 1,3,5-benzenetricarboxylic acid is 0.01 to 0.2 mol / L.

[0013] Furthermore, the inert gas described in step (1) includes nitrogen, helium, argon, and neon.

[0014] Furthermore, the programmed temperature rise in step (1) is 1-5°C min -1 The rate of heating.

[0015] Furthermore, the acid in step (2) is one of HCl, H2SO4 and HNO3, and the concentration of the acid solution is 2 to 10 mol / L.

[0016] Furthermore, the organic solvent in step (3) includes carbon disulfide, benzene, and quinoline.

[0017] Furthermore, in step (3), the mass ratio of Se to Fe2O3@NC composite material is 1:1 to 5:1.

[0018] Another aspect of the present invention provides a Fe2O3-Se@NC material prepared by the above preparation method.

[0019] The present invention also provides the use of the Fe2O3-Se@NC material as a negative electrode material for sodium ion batteries and / or potassium ion batteries.

[0020] The beneficial effects of the present invention compared with the prior art are as follows:

[0021] 1. The synthesis of Se electrodes is often carried out by a high-temperature melting method, which easily causes waste of selenium and it is difficult to avoid residual selenium on the surface. The present invention provides a low-temperature stirring adsorption method, which can realize the preparation of quantitative Se electrodes by low-temperature operation, and can achieve a good composite of Se and the complex, while avoiding waste of selenium.

[0022] 2. In the Fe2O3-Se@NC composite material prepared by the present invention, Se particles are anchored and dispersed on a nanoscale carbon substrate, which can achieve rapid electron and ion transmission, and the co-doping characteristics of nitrogen and Fe2O3 are conducive to inhibiting the shuttling of polyselenides. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0024] Figure 1 XRD patterns of synthesized Fe2O3@NC and HCl-Fe2O3@NC washed with hydrochloric acid.

[0025] Figure 2 XRD patterns of synthesized Fe2O3-Se@NC and commercial Se element.

[0026] Figure 3This is the rate performance diagram of the synthesized Fe2O3-Se@NC.

[0027] Figure 4 The synthesized Fe2O3-Se@NC -1 Plot of long cycles at different current densities. DETAILED DESCRIPTION

[0028] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0029] Example 1

[0030] (1) Synthesis of Fe2O3@NC composite material (Fe2O3@NC): 1.0 g of polypropylene glycol and ethylene oxide addition polymer (F127) and 1.0 g of dopamine hydrochloride (DA) were dissolved in a mixed solution of 100 mL of water and ethanol (volume ratio of 1:1), and stirred vigorously at room temperature to obtain a clear solution. Then 5.8083 g of Fe(NO3)3·9H2O was added to the above solution at a stirring rate of 500 rpm to form a clear solution. After stirring for 30 minutes, 3.0212 g of 1,3,5-benzenetricarboxylic acid was added to the above mixture, and the reaction was stirred continuously for 30 minutes. After centrifugation to obtain the separated product, it was washed at least 3 times with a mixture of water and ethanol and dried to obtain polymer nanoparticles;

[0031] In order to obtain the Fe2O3@NC composite, the synthesized polymer nanoparticles were placed in a porcelain boat, put into a tube furnace, and then heated at 1 °C min in an Ar atmosphere. -1 The heating rate was set to 600℃ and calcined for 3h. After cooling to room temperature, the magnetic boat was taken out of the tube furnace and placed in the air for 30 minutes to obtain Fe2O3@NC.

[0032] (2) Synthesis of Fe2O3@NC (HCl-Fe2O3@NC) composite material co-doped with porous nitrogen and Fe2O3: The Fe2O3@NC prepared in step (1) was added to an 8 mol / L HCl solution. During the addition process, the solution must be heated and stirred until it is clear. The mouth of the glass was sealed with a sealing tape to prevent the volatilization and evaporation of hydrochloric acid. The solution was stirred at 65°C for 7 h to obtain a Fe2O3@NC composite material co-doped with porous nitrogen and Fe2O3.

[0033] (3) Synthesis of Fe2O3-Se@NC composite material co-doped with porous nitrogen and Fe2O3: 0.3 g of Se element was completely dissolved in carbon disulfide, then 0.15 g of the composite material prepared in step (2) was added to the above solution and stirred for 2 h to evaporate and remove carbon disulfide, and finally dried at 65°C to obtain Fe2O3-Se@NC composite.

[0034] Figure 1 This indicates that the nitrogen-doped carbon and Fe2O3 composite (Fe2O3@NC) was successfully synthesized, and the composite (HCl-Fe2O3@NC) after acid washing no longer shows the peak of Fe2O3, indicating that most of the Fe2O3 has been removed by acid washing.

[0035] Figure 2 This indicates that the Fe2O3-Se@NC composite was successfully synthesized after stirring evaporation at room temperature, and the crystallinity of Se in the composite was still high.

[0036] The Fe2O3-Se@NC prepared in Example 1 was used as the active material of the sodium ion half-cell, a sodium sheet with a diameter of 1.6 mm was used as the counter electrode, a glass fiber membrane was used as the separator, 1 M NaPF6 was used as the supporting electrolyte, and the solvent DIGLYME was used as the electrolyte to assemble the sodium / Fe2O3-Se@NC half-cell. -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , 5A g -1 , 10A g -1 and 20A g -1 The charge and discharge rate performance was tested at 5A g -1 A high current long cycle test was carried out at a current density of .

[0037] Figure 3 This shows that the rate performance of the Fe2O3-Se@NC composite is good. -1 There is still 266.8mAh g -1 Specific capacity.

[0038] Figure 4 It shows that the Fe2O3-Se@NC composite has good cycling stability at 5A g -1 After 1009 cycles at a current density of 305.1 mAh g -1 Specific capacity.

[0039] Embodiment 2-11:

[0040] The preparation process of the carbon carrier nitrogen-doped Fe2O3@NC composite material, the process of assembling it into a battery, and the performance testing process are the same as those in Example 1, except for the amount of dopamine hydrochloride, the concentration of hydrochloric acid, the pickling time, the ratio of Se to HCl-Fe2O3@NC, and the solvent used to dissolve Se. The relevant data are shown in Table 1. The performance test data of the prepared sodium ion battery are shown in Table 3.

[0041] When the Fe2O3@NC synthesized in different steps were subjected to electrochemical tests, the Fe2O3-Se@NC synthesized in Example 1 showed the best electrochemical activity. The prepared composite material showed a high rate performance at 20 A·g -1 At a current density of 266.8 mAh g -1 The specific capacity at 5A·g -1 After 1009 cycles at a current density of 305.1 mAh·g -1 It has a high specific capacity and good rate performance and high current and long cycle performance.

[0042] Comparative Examples 1-6:

[0043] The preparation process of the carbon carrier nitrogen-doped Fe2O3@NC composite material, the process of assembling it into a battery, and the performance testing process are different from those in Example 1, except for the amount of dopamine hydrochloride, the concentration of hydrochloric acid, the pickling time, the ratio of Se to HCl-Fe2O3@NC, and the method of composite selenium used. The relevant data are shown in Table 2. The performance test data of the prepared sodium ion battery are shown in Table 3.

[0044] Table 1. Preparation process parameters of the composite materials of Examples 1-11

[0045]

[0046] Table 2. Preparation process parameters of the composite materials of Comparative Examples 1-8

[0047]

[0048] Table 3. Performance test results of the composite materials of Examples 1-11 and Comparative Examples 1-8

[0049]

[0050] It can be seen from the experimental results that the change in the amount of dopamine hydrochloride does not significantly affect the proportion of Fe2O3 in the entire composite, which mainly serves as a nitrogen source. The preferred concentration of dopamine hydrochloride is 2 to 20 (mg / ml).

[0051] It can be seen from the experimental results that the proportion of Fe2O3 in the final composite mainly depends on the concentration of hydrochloric acid and the pickling time. The preferred hydrochloric acid concentration in the present invention is 2-10mol / L, and the preferred pickling time is 2-12h. When the hydrochloric acid concentration is too low or the pickling time is short, the content of iron oxide after pickling will be relatively high, and the volume expansion of iron oxide during the charge and discharge process will be large, resulting in poor overall electrochemical performance; when the pickling time is too long, the content of iron oxide after pickling will be relatively low, thereby weakening the polar bond effect of Fe2O3-Se@NC on polyselenide, thereby causing the overall performance to deteriorate.

[0052] The experimental results show that the amount of Se in the final composite depends mainly on the ratio of Se to HCl-Fe2O3@NC during the synthesis, and the preferred ratio of Se to HCl-Fe2O3@NC in step (3) is 1:1-5:1. When the selenium content in the composite is too low, the polar bonding effect of Fe2O3-Se@NC on the polyselenide is stronger, the cycle stability is higher, but the rate performance is reduced; when the selenium content is too high, the polar bonding effect of Fe2O3-Se@NC on the polyselenide is weakened due to the high selenium content, thereby reducing the overall performance.

[0053] The experimental results show that when a solvent that can dissolve Se is used, the electrochemical performance of the synthesized composite will not change. At the same time, compared with the conventional high-temperature melting method to prepare the composite, due to the high viscosity and low fluidity of selenium in the molten state during the high-temperature melting process, it is difficult for selenium to quickly enter the carrier material. Most of the selenium is deposited on the surface of the carrier material, causing the carrier to lose its function of binding selenium, resulting in a decrease in the overall electrochemical performance of the battery.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a porous Fe2O3-Se@NC material, characterized in that: The following steps are involved: (1) dissolving a polypropylene glycol-ethylene oxide addition polymer and dopamine hydrochloride in a mixed solution of water and alcohol to obtain a clear solution, adding an iron salt or its hydrate under stirring to form a clear solution, adding 1,3,5-benzenetricarboxylic acid, stirring and reacting for 10 to 150 minutes, centrifuging to obtain a separate product, washing it with a mixed solution of water and alcohol for at least 3 times, and drying to obtain polymer nanoparticles, heating the obtained polymer nanoparticles to 500 to 800°C in an inert gas atmosphere, calcining for 2 to 5 hours, cooling to room temperature, and placing it in air for 20 to 60 minutes to obtain Fe2O3@NC; (2) adding the Fe2O3@NC prepared in step (1) into an acid solution and stirring at 40-100°C for 2-12 h to obtain a porous nitrogen and Fe2O3 co-doped Fe2O3@NC composite material; (3) adding the Fe2O3@NC composite material prepared in step (2) into an organic solvent containing Se, stirring and evaporating the organic solvent, and drying to obtain a Fe2O3-Se@NC material; The concentration of dopamine hydrochloride in step (1) is 2 to 20 mg / ml; The concentration of the acid solution in step (2) is 2-10 mol / L; In step (3), the mass ratio of Se to Fe2O3@NC composite material is 1:1~5:

1.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the polypropylene glycol and ethylene oxide addition polymer to dopamine hydrochloride is 1:2-2:1, and the final concentration of the polypropylene glycol and ethylene oxide addition polymer is 1-50 g / L.

3. The preparation method according to claim 1, characterized in that: The alcohols described in step (1) include methanol, ethanol, propanol and butanol, and the volume ratio of water to alcohols is 1:2 to 2:

1.

4. The preparation method according to claim 1, characterized in that The iron salt in step (1) is one or more of ferric sulfate, ferric chloride, and ferric nitrate, and the final concentration of iron ions is 0.01-0.2 mol / L; the final concentration of 1,3,5-benzenetricarboxylic acid is 0.01-0.2 mol / L.

5. The preparation method according to claim 1, characterized in that The inert gas in step (1) includes nitrogen, helium, argon, and neon; the programmed temperature is 1-5 °C min -1 The rate of heating.

6. The preparation method according to claim 1, characterized in that: The acid in step (2) is one of HCl, H2SO4 and HNO3.

7. The preparation method according to claim 1, characterized in that: The organic solvent in step (3) includes carbon disulfide, benzene, quinoline, and dichloromethane.

8. Fe2O3-Se@NC material obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the Fe2O3-Se@NC material according to claim 8 as a negative electrode material for alkali metal batteries.

Citation Information

Patent Citations

  • Nitrogen-doped carbon-coated molybdenum selenide / graphene core-shell array sandwich structure composite material, preparation method and application thereof

    CN105914374A

  • Nitrogen-selenium co-doped porous carbon sphere, sodium ion battery negative electrode material, and preparation methods and applications thereof

    CN112582617A